Influence on cheese proteolysis and sensory characteristics of non-starter lactobacilli strains with probiotic potential - Milesi, Maria Mercedes (2009)
Abstract The contribution to cheese proteolysis and sensory profile of four potentially probiotic non-starter lactobacilli strains was assessed in two different models: soft and semi-hard cheeses. All the strains were able to grow in both types of cheese, where they maintained high levels during ripening. Overall, adjunct cultures of Lactobacillus rhamnosus showed the strongest influence in peptidolysis, which was verified by changes in peptide profiles and increase of free amino acids concentration. Nevertheless, some cheeses treated with L. rhamnosus also showed post-acidification during ripening and decreased sensory characteristics compared to controls. Cheeses with adjunct cultures of Lactobacillus casei I90 and Lactobacillus plantarum I91 exhibited, in general, an intermediate level of peptidolysis between control and L. rhamnosus-added cheeses; their sensory characteristics were preserved or improved, and they did not show any defects. Adjunct cultures showed similar trends in both models, confirming L. casei I90 and L. plantarum I91 as the most performing adjunct cultures for cheese-making among the strains.